The impact of blood donation on blood counts and ferritin levels: A multi-center study from the Eastern Mediterranean region. (June 2021) - Hindawi, Salwa; Badawi, Maha; Hussein, Deema; Al-Riyami, Arwa Z.; Daghman, Nureddin A.; Rafie, Nawal Ibrahim; Belgasm, Najat Mohmod; Al Zaabi, Eiman; Oumeziane, Naima
Abstract: Regular donation of whole blood may lead to iron deficiency. In this study, we aimed to assess the impact of frequent whole blood donation on hematological parameters. Whole blood donors were enrolled from four blood banks located in Saudi Arabia, United Arab Emirates (UAE), Libya and Oman, between 2016 and 2017. SPSS version 21.0 was used to generate descriptive and inferential statistics. A total number of 3096 blood donors were screened (males 93.8 %, females; 6.2 %), with a mean donor age of 35.29 ± 9.31 years. For male blood donors, the majority (1073) had 1−3 previous donations. Increased frequency of donations was significantly associated with increases in age and weight, decreases in Hemoglobin (Hb) and ferritin measures, and increases in Red Blood Cells (RBC) counts. A General Linear Model (GLM) adjusted for age and weight indicated negative impacts on White Blood Cells (WBC) counts and ferritin. A weak correlation between the Hb and ferritin levels was observed (r = 0.160, P > 0.001). For female donors, the majority (63 out of 114) were first time donors. Increased frequency of donations was significantly associated with an increase in age and a decrease in HCT readings. A GLM adjusted for age and weight indicated a negative impact on ferritin. A strong correlation was observed between the Hb and ferritin levels for the most frequent female donors (r = 0.636, P > 0.001). In conclusion, regular whole blood donation impacts hematological parameters in particular the levels of ferritin in the serum.